RAS in Pregnancy and Preeclampsia and Eclampsia - M. Rodriguez; J. Moreno; J. Hasbun (International Journal of Hypertension)
Preeclampsia is a common disease of pregnancy characterized by the presence of hypertension and commitment of many organs, including the brain, secondary to generalized endothelial dysfunction. Its etiology is not known precisely, but it involved several factors, highlighting the renin angiotensin system (RAS), which would have an important role in the origin of multisystem involvement. This paper reviews the evidence supporting the involvement of RAS in triggering the disease, in addition to the components of this system that would be involved and how it eventually produces brain engagement.